In Situ Tracking of Nanoparticles During Electrophoresis in Hydrogels Using a Fiber-Based UV-Vis System - Matthäus Barasinski; Valentin Jasper; Marion Görke; Georg Garnweitner (Powders)
Gel electrophoresis is a powerful method for the separation of nanoparticulate suspensions into several fractions with distinct particle properties. To monitor particle migration through the three-dimensional net structure of the gel and gain insights about the separation process, this study introduces a self-designed fiber-based UV-Vis measurement system equipped with five probes for the sequential in situ recording of absorption spectra. The system was employed to investigate the migration and separation of Au and Fe3O4 particles within hydrogels of varying agarose concentrations (0.15–0.50 wt.-%), revealing an increase in scattering with higher agarose content. The identification of specific particle fractions with a spherical or rod-shaped morphology was successfully achieved within the gels due to characteristic absorption peaks, allowing the real-time observation of particle separation. For the separation of a binary mixture, an adequate migration distance is needed according to the difference in the electrophoretic mobility of the two samples. The particle tracking and an additional mathematical deconvolution allowed the analysis of mixed particle samples within the gel so that their weight ratio could be determined. Finally, the system was calibrated for the determination of the particle concentration within the gel matrix, quantitatively revealing the particle concentration at a specific position in the gel.